Character Formation through Islamic Religious Education Teachers' Roles: A Qualitative Study of Students' Responsibility - Andri; Indah Muliati (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
This study aims to explore how Islamic Religious Education (Pendidikan Agama Islam dan Budi Pekerti [PAI BP]) teachers cultivate students' responsibility by examining the multiple professional roles they perform during classroom instruction and character education. The study addresses the limited understanding of responsibility formation as a dynamic educational process rather than as the outcome of isolated instructional strategies. This research employed a qualitative approach using a single-case study design conducted at SMP Negeri 1 Kecamatan Situjuah Limo Nagari, Indonesia. Data were collected through classroom observations, semi-structured interviews, and document analysis involving one Islamic Religious Education teacher and twenty junior high school students selected through purposive sampling. The data were analysed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing, while trustworthiness was ensured through triangulation, prolonged engagement, and member reflection. The findings revealed that students' responsibility was cultivated through six interconnected teacher roles: educator, role model, motivator, evaluator, mediator, and facilitator. These roles operated synergistically through classroom habituation, exemplary behaviour, motivational support, formative assessment, mediation of Islamic values, and student-centred learning experiences. Responsibility emerged not merely from moral instruction but from continuous interactions and authentic educational practices embedded in everyday school life. Unlike previous studies that examined teachers' roles separately, this study conceptualizes responsibility formation as a multifaceted character-building process in which multiple professional roles interact dynamically to foster students' responsibility within Islamic Religious Education. This study enriches the literature on character education by proposing an integrated conceptual framework that combines character education, social learning, and sociocultural perspectives. The findings also provide practical implications for teachers, school leaders, and policymakers in designing more comprehensive and sustainable character education programmes.